Analytical chemistry - Kealey, D. ; Haines, P. J. (BIOS, 2020)
The nature and scope of analytical chemistry --|tAssessment of data --|tAnalytical reactions in solution --|tSeparation techniques --|tSpectrometric techniques --|tCombined techniques --|tThermal methods --|tSensors, automation and computing.